2019
DOI: 10.1084/jem.20180823
|View full text |Cite
|
Sign up to set email alerts
|

Human colon organoids reveal distinct physiologic and oncogenic Wnt responses

Abstract: Constitutive Wnt activation upon loss of Adenoma polyposis coli (APC) acts as main driver of colorectal cancer (CRC). Targeting Wnt signaling has proven difficult because the pathway is crucial for homeostasis and stem cell renewal. To distinguish oncogenic from physiological Wnt activity, we have performed transcriptome and proteome profiling in isogenic human colon organoids. Culture in the presence or absence of exogenous ligand allowed us to discriminate receptor-mediated signaling from the effects of CRIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 89 publications
(135 reference statements)
5
57
0
Order By: Relevance
“…The protocol of organoid culture has been optimized and widely implemented by various research groups ( Ettayebi et al., 2016 ; Li et al., 2014 ). However, due to the complex culture condition ( Holloway et al., 2019 ), inter-heterogeneity of the biopsy-derived organoids has often been observed between organoid lines ( Michels et al., 2019 ; Urbischek et al., 2019 ) or the quality of conditioned medium for supplying the major morphogens ( Fatehullah et al., 2016 ). Various efforts have been made to overcome these challenges by increasing the number of experimental replicates, testing multiple lines, and validating the effect of different passage numbers to improve experimental statistics.…”
Section: Introductionmentioning
confidence: 99%
“…The protocol of organoid culture has been optimized and widely implemented by various research groups ( Ettayebi et al., 2016 ; Li et al., 2014 ). However, due to the complex culture condition ( Holloway et al., 2019 ), inter-heterogeneity of the biopsy-derived organoids has often been observed between organoid lines ( Michels et al., 2019 ; Urbischek et al., 2019 ) or the quality of conditioned medium for supplying the major morphogens ( Fatehullah et al., 2016 ). Various efforts have been made to overcome these challenges by increasing the number of experimental replicates, testing multiple lines, and validating the effect of different passage numbers to improve experimental statistics.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we used NGS RNA-Seq data derived from 458 colon cancer and 167 rectal tumors from TCGA as provided by the NCI-GDC [28], and we generated preranked lists of genes according to their Pearson correlation with LARGE2 gene expression (data not shown). By GSEA, we found that two independent sets of Wnt target genes [15,49] and a recently described oncogenic/ intrinsic Wnt signature [50] were enriched among the genes positively correlated with LARGE2 expression (Fig. 2D,E and Additional file 4C-E).…”
Section: Large2 Correlates With Active Wnt Signaling and Hcosc Gene Ementioning
confidence: 83%
“…To address these issues, 3D cell culture models are a reliable alternative, providing experimentally accessible human models to study the biological processes of cancer. Several 3D culture platforms such as spheroids, organoids, hydrogels, 3D scaffolds, 3D bio-printing, and microfluidics have attempted the recreation of certain aspects of tumor microenvironments present in tissues including the brain [30][31][32][33][34][35][36], breast [37][38][39][40][41][42][43], ovarian [44][45][46][47][48][49][50][51], bone [52][53][54][55][56][57][58], liver [59][60][61][62][63][64][65], lung [66][67][68][69][70][71][72], colon [73][74][75][76]…”
Section: Mimicking Tme In Three-dimensionsmentioning
confidence: 99%